Timeliness of the Annual Member Meeting (RAT) In the Woman Cooperative in Jombang Regency - Mutiarni, Rita (Eksis: Jurnal Riset Ekonomi dan Bisnis, 2019)
Abstract Jombang Regency which consists of 21 districts has a woman cooperative (Kopwan) spread in 301 villages and 5 (five) villages. However, not all these organzation are in good health and are able to hold RATs on time for various reasons. This study aims to: 1) Determine timeliness in organizing RATs for woman cooperatives in Jombang in 2017, 2) Factors supporting the timeliness of the implementation of RATs. This type of research is a qualitative research with an observation method involving 90 respondents as research samples. From the results of the study note that: 1) Of 90 woman Cooperatives spread over 21 districts, as many as 50 woman cooperatives or 55% were able to hold a RAT on time, on January and February in the following year, while the rest is not timely and not even organize RAT, 2) Factors supporting the timeliness of the organization RATs are: a) Routinely attending training at the woman Cooperative Center (Puskopwan), b) Routinely reporting Financial Statements Every Month to Puskopwan and the Jombang Cooperatives and Micro Enterprises and c) Using electronic (computerized) registration aids